Synthesis of Sitagliptin Intermediate by a Multi-Enzymatic Cascade System Using Lipase and Transaminase With Benzylamine as an Amino Donor - Khobragade, Taresh P.; Sarak, Sharad; Pagar, Amol D.; Jeon, Hyunwoo; Giri, Pritam; Yun, Hyungdon (Frontiers in Bioengineering and Biotechnology, 2021)
Herein, we report the development of a multi-enzyme cascade using transaminase (TA), esterase, aldehyde reductase (AHR), and formate dehydrogenase (FDH), using benzylamine as an amino donor to synthesize the industrially important compound sitagliptin intermediate. A panel of 16 TAs was screened using ethyl 3-oxo-4-(2,4,5-trifluorophenyl) butanoate as a substrate (1). Amongst these enzymes, TA from Roseomonas deserti (TARO) was found to be the most suitable, showing the highest activity towards benzylamine (~70%). The inhibitory effect of benzaldehyde was resolved by using AHR from Synechocystis sp. and FDH from Pseudomonas sp., which catalyzed the conversion of benzaldehyde to benzyl alcohol at the expense of NAD(P)H. Reaction parameters, such as pH, buffer system, and concentration of amino donor, were optimized. A single whole-cell system was developed for co-expressing TARO and esterase, and the promoter engineering strategy was adopted to control the expression level of each biocatalyst. The whole-cell reactions were performed with varying substrate concentrations (10-100 mM), resulting in excellent conversions (ranging from 72%-91%) into the desired product. Finally, the applicability of this cascade was highlighted on gram scale, indicating production of 70% of the sitagliptin intermediate with 61% isolated yield. The protocol reported herein may be considered an alternative to existing methods with respect to the use of cheaper amine donors as well as improved synthesis of (R) and (S) enantiomers with the use of non-chiral amino donors.